Intravitreal steroid implants in the management of noninfectious intermediate and posterior uveitis - Sarjak M Shah; Priya Prabhu; Jyotirmay Biswas (Indian Journal of Ophthalmology)
The management of intermediate and posterior uveitis poses a significant challenge of achieving adequate drug concentrations in the posterior segment over the chronic nature of the disease. Systemic agents seldom reach effective drug levels, and even with low maintenance or tapering doses, it is hard to avoid systemic toxicity. The use of intravitreal and periocular injections is often unable to prevent recurrences due to their short half-life. Since the emergence of intravitreal implants (Vitrasert, Retisert), it has become possible to circumvent these therapeutic challenges. A detailed review in the PubMed index yielded 155 articles, of which 22 were analyzed based on exclusion criteria. A recent shift from surgically sutured to minimally invasive injectable implants mainly indicated for noninfectious uveitis is evident from the literature. This review article also provides insights into dexamethasone (Ozurdex) and recent fluocinolone acetonide (Yutiq, Iluvien) implants with particular emphasis on their improved safety and efficacy. Dexamethasone implants favor the therapeutic goal of prevention of recurrences, whereas the use of fluocinolone implants helps to attain better visual outcomes due to their longer duration of action. Thus, the review provides recent literature supporting the role and indication of sustained release intravitreal implants in the management of noninfectious intermediate and posterior uveitis.